2023
DOI: 10.7150/thno.83353
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3K27 methyltransferase EZH2 regulates apoptotic and inflammatory responses in sepsis-induced AKI

Abstract: Rationale: The role of histone methylation modifications in renal disease, particularly in sepsis-induced acute kidney injury (AKI), remains unclear. This study aims to investigate the potential involvement of the histone methyltransferase zeste homolog 2 (EZH2) in sepsis-induced AKI and its impact on apoptosis and inflammation. Methods: We first examined the expression of EZH2 in the kidney of sepsis-induced AKI (LPS injection) mice and LPS-stimulated tubular epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Moreover, the protective effect of EZH2 inhibition with 3-DZNep has been demonstrated in kidney injuries. In a model of sepsis-induced AKI, inhibition of EZH2 expression could reduce the apoptotic and inflammatory responses of renal TEC, alleviating AKI by mitigating the transcriptional inhibition of SOX9 [ 34 ]. Furthermore, EZH2 inhibition was proven to suppress cisplatin-induced renal TEC apoptosis and AKI by maintaining the expression level of E-calmodulin [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the protective effect of EZH2 inhibition with 3-DZNep has been demonstrated in kidney injuries. In a model of sepsis-induced AKI, inhibition of EZH2 expression could reduce the apoptotic and inflammatory responses of renal TEC, alleviating AKI by mitigating the transcriptional inhibition of SOX9 [ 34 ]. Furthermore, EZH2 inhibition was proven to suppress cisplatin-induced renal TEC apoptosis and AKI by maintaining the expression level of E-calmodulin [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the protective effect of EZH2 inhibition with 3-DZNep have been demonstrated in kidney injuries. In a model of sepsis-induced AKI, inhibition of EZH2 expression could reduce the apoptotic and in ammatory responses of renal TEC, alleviating AKI by mitigating the transcriptional inhibition of SOX9 [33]. Furthermore, EZH2 inhibition was proven to suppress cisplatin-induced renal TEC apoptosis and AKI by maintaining the expression level of E-calmodulin [34].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous results, researchers found that overexpression of SPRY4 induces apoptosis in human colorectal cancer cell lines (SW480), increasing the apoptotic rate, upregulating the expression of pro-apoptotic proteins (Bax, Cleaved Caspase-3), and downregulating the expression of anti-apoptotic proteins (Bcl2 and EZH2) ( 8 ). It has been reported that silencing EZH2 can reduce apoptosis and inflammatory responses in renal tubular epithelial cells ( 39 ). Therefore, it is speculated that SPRY4 may induce apoptosis by inhibiting EZH2.…”
Section: Spry4 Functionmentioning
confidence: 99%